PERLINDUNGAN HUKUM TERHADAP PEREMPUAN YANG MENGALAMIKEKERASAN DALAM RUMAH TANGGA (KDRT) DI TENGAH PANDEMICOVID-19 - Dr. Putu Sekarwangi Saraswati, SH, MH (Jurnal Ilmiah Raad Kertha, 2021)
The world is currently being faced with a very horrendous event that is a Corona Virus disease. This disease has spread rapidly to all parts of the countries in the world including Indonesia. Because of this Corona Virus, Indonesia has adopted a policy, namely Large-Scale Social Restrictions, this policy has an impact on all sectors of the economy-shial in Indonesia. Because this policy also all Indonesian people do not work and stay at home. This is the main trigger for an act of domestic violence that occurs. Because all people do not work and just stay at home, triggering a dispute that occurs between husband and wife rhich results in an act of violence committed by the husband to his wife. Many factors are the reason why domestic violence occurs, one of which is because of declining economic income or because husbands, wives experience stress because of this condition. Extra efforts are needed to avoid the problem of dosmetic violence that occurs in the pandemic covid-19. One of them by emphasizing the existence of Law Number 23 of 2004